STUDI KOMPUTASI VARIASI PARAMETER GEOMETRIS PROPULSION MODULE PADA AZIPOD PROPULSION SYSTEM - Achmad Zainudin Amra (2023)
The ship propulsion system is one of the most important aspects of a vessel. Therefore, a high-efficiency propulsion system is highly sought after. The Azimuthing Podded Drive (AZIPOD) propulsion system is introduced as one of the latest innovations to enhance ship operation efficiency, where the selection of geometric parameter shapes for AZIPOD is crucial in achieving optimal propulsion system efficiency. Hence, a detailed investigation of the geometric parameter shapes of AZIPOD must be conducted regarding the hydrodynamic performance of the propulsor. In this study, simulations will be carried out to determine the most optimal shape for an AZIPOD propulsion system by varying the aft taper angle geometric parameter at 5°, 10°, and 15°, as well as the fore taper angle at 5° and 10°. The simulations will be performed using Computational Fluid Dynamics (CFD) software, ANSYS FLUENT. Based on the conducted analysis, it is found that the most optimal shape resulting from the variation in geometric parameters is an AZIPOD with a 10° aft taper angle. This variation in the AZIPOD model yields an average thrust force increase of 1.183% and an average torque increase of 1.016%. Furthermore, the average efficiency of this model shows an increase of 0.272%.